Ocular prosthesis for post pediatric enucleation: a case report: Prostesis okular untuk pasca enukleasi anak: sebuah laporan kasus - Vinsensia Launardo; Eka Fibrianti; Irsal Wahyudi; Eri Hendra Jubhari (Makassar Dental Journal, 2022)
Losing an eyeball is a traumatic event both medically and psychologically that can cause functional, psychological, and aesthe-tic problems. Ocular prosthesis is part of a whole rehabilitative treatment after the surgery. This article describes the procedure to make a permanent ocular prosthesis to improve appearance, physical and psychological post surgery. A 3-year-old female patient came to Halimah Dg. Sikati Makassar Dental Hospital that was referred by an ophthalmologist after losing her right eye-ball to enucleation procedure for stage 2 tumor at the tender age of 8 months and wishes to have a permanent ocular prosthesis to restore appearance and self-confidence. Ocular prosthesis can help ease the psychological trauma and burden of losing the eyeball. It was concluded that restores the aesthetic appearance of the eyeball can increase the patient's confidence so she can function and feel better socially.